COVID-19 and business continuity - learning from the private sector and humanitarian actors in Kenya. (October 2021) - Schmid, Benjamin; Raju, Emmanuel; Jensen, Peter Kjær Mackie
Abstract: The COVID-19 pandemic has caused unprecedented disruption to different communities and organizations globally. Evidence on the potential role of business continuity for pandemic resilience remains scattered, particularly in low- and middle-income countries. In this case study on COVID-19, based on qualitative interviews with private and humanitarian actors in Kenya, gaps in formal Business Continuity approaches emerged. The actors' continuity was mostly driven by pre-existing conditions and organizational agility, while major differences between humanitarian and private actors' business continuity were observed. This paper's findings highlight the opportunities of a simplified, agile, and accessible business continuity and its potential applicability during future disruptions. Highlights: Pre-existing conditions and organizational agility as the key factors to business continuitymanagement. Humanitarian organizations often perceived business continuity as inherent to their work ratherthan as a business process. Major differences of BCM conceptualisation between humanitarian and private sector actors were observed. COVID-19 recovery must place emphasis on business continuity and requires a focused change to the "resilience" narrative-